Double-diffusive convection of synovial (couple-stress) fluid in the presence of hall current through a porous medium - Singh, Mahinder (Zielona Góra: Uniwersytet Zielonogórski)
An investigation made on the effect of Hall currents on double-diffusive convection of a compressible synovial (couple-stress) fluid in the presence of a horizontal magnetic field through a porous layer is considered. The analysis is carried out within the framework of linear stability theory and normal mode technique. A dispersion relation governing the effects of viscoelasticity, compressibility, magnetic field and porous layer is derived.
Keywords: compressibility; synovial fluid; double- diffusive convection; porous medium and Hall current